2016
DOI: 10.1016/j.tem.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Dichotomous Effect of Chronic Stress on Obesity

Abstract: Obesity and metabolic diseases are linked to chronic stress and low socio-economic status. The mechanistic link between stress and obesity has not been clarified, partly due to the inherent complexity exemplified by the bidirectional effect of stress on eating and body weight. Recent studies focusing on adaptive-thermogenesis and brown adipose tissue (BAT) function support a dichotomous relationship to explain the impact of stress on obesity: stress promotes obesity in the presence of hyperphagia and unchanged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 100 publications
(171 reference statements)
2
74
0
5
Order By: Relevance
“…Gilbert and Allan (1998) have used the term 'entrapment' to refer to these inescapable, negative life situations and suggested that low mood, anxiety disorders and depression can be an expression of inability (or believed to be so) to escape from aversive thoughts/feelings or external circumstances (Carvalho et al, 2013). Indeed, the most widely used and effective social stressors in animal models are defeat in aggressive encounters and chronic subordination due to unescapable exposure to the dominant animal, which induce psychopathological changes and depressive-like behavior in male mice, accompanied by consistent alterations of hormonal, physiological, behavioral, immune and metabolic responses (Bartolomucci et al, 2004a(Bartolomucci et al, ,b,c, 2005Razzoli and Bartolomucci, 2016). Because of its congruence with the human condition, the defeat-induced loss of status in mice and rats has been proposed as a model of loss of self-esteem and depression in humans that may parallel human psychiatric disorders related to negative emotions provoked by loss of social role, resources, and adverse social environment (Blanchard et al, 1995a,b;Willner et al, 1995;Marrow and Brain, 1998;Blanchard et al, 2001;Huhman, 2006).…”
Section: Conclusion: In Search For a Female Mouse Modelmentioning
confidence: 99%
“…Gilbert and Allan (1998) have used the term 'entrapment' to refer to these inescapable, negative life situations and suggested that low mood, anxiety disorders and depression can be an expression of inability (or believed to be so) to escape from aversive thoughts/feelings or external circumstances (Carvalho et al, 2013). Indeed, the most widely used and effective social stressors in animal models are defeat in aggressive encounters and chronic subordination due to unescapable exposure to the dominant animal, which induce psychopathological changes and depressive-like behavior in male mice, accompanied by consistent alterations of hormonal, physiological, behavioral, immune and metabolic responses (Bartolomucci et al, 2004a(Bartolomucci et al, ,b,c, 2005Razzoli and Bartolomucci, 2016). Because of its congruence with the human condition, the defeat-induced loss of status in mice and rats has been proposed as a model of loss of self-esteem and depression in humans that may parallel human psychiatric disorders related to negative emotions provoked by loss of social role, resources, and adverse social environment (Blanchard et al, 1995a,b;Willner et al, 1995;Marrow and Brain, 1998;Blanchard et al, 2001;Huhman, 2006).…”
Section: Conclusion: In Search For a Female Mouse Modelmentioning
confidence: 99%
“…BAT activation is regulated by central nervous system neural networks which respond reflexively to the thermal afferent signals from skin thermoreceptors . These networks mount an activation of the sympathetic nerves that innervate the BAT, classically in response to either cold acclimation, acute cold exposure or stress . Brown adipocyte activity is primarily regulated by the sympathetic nerve‐derived norepinephrine (NE) signaling through β‐adrenergic receptors (βARs) which results in activation of uncoupling protein 1 (UCP1) and consequent conversion of energy to heat .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to stress results in wide‐ranging effects on physiology and behaviour. In particular, energy homeostasis is profoundly affected by acute and chronic stress (Ulrich‐Lai and Ryan, ; Razzoli and Bartolomucci, ). These effects are complex and depend on a variety of factors such as stressor type, duration and frequency (Maniam and Morris, ; Razzoli et al ., ).…”
Section: Introductionmentioning
confidence: 99%